The roles of teachers’ beliefs and instructional practices in students’ mathematical mindset - Piyakun, Araya; Phusee-Orn, Songsak (Frontiers in Education, 2025)
IntroductionMathematics education development is an urgent topic, with an emphasis on increasing students’ motivation to learn mathematics.MethodsThis study aimed to investigate the impacts of teachers’ mathematical mindset, task values, and instructional practices on students’ mathematical mindset, using students’ perceived instructional practices as a mediator. The participants consisted of 96 teachers and 936 secondary school students. The research instruments included a mathematical mindset scale for teachers and students, a task value scale for teachers, an instructional practice scale for teachers, and a perceived instructional practice scale for students. The statistics for analyzing data included mean, standard deviation, and Structural Equation Modeling (SEM).ResultsThe finding revealed that, from most to least, the variables that mutually influenced students’ mathematical growth mindset were students’ perceived instructional practices, teachers’ instructional practices, teachers’ values, and teachers’ mathematical growth mindset.DiscussionThe study’s findings can serve as a framework for developing teachers, who are essential to mathematics education and enhancing secondary school students’ motivation for mathematical learning.